2014
DOI: 10.1039/c4tc00139g
|View full text |Cite
|
Sign up to set email alerts
|

Two-component solution processing of oxide semiconductors for thin-film transistors via self-combustion reaction

Abstract: The self-combustion of In and Zn precursors coordinated with fuel and oxidizer ligands is utilized for high performance IZO TFTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
77
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(79 citation statements)
references
References 36 publications
2
77
0
Order By: Relevance
“…In previous spin-CS studies, very smooth surface topologies were achieved for thin (5-nm) single-layer/ multilayer films (ρ RMS = 0.2-0.5 nm) (2,16). However, thicker (20-to 50-nm) single-layer films are significantly more porous and rougher (ρ RMS > 1 nm) (2,16), reminiscent of conventional thick sol-gel oxide films (17)(18)(19)(20)(21). In this work, atomic force microscopy and SEM images show that optimized single-layer SCS growth yields smooth thicker oxide films ( 5 at low operating voltages of 2 V owing to the enhanced capacitance of the gate dielectric ( Fig.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…In previous spin-CS studies, very smooth surface topologies were achieved for thin (5-nm) single-layer/ multilayer films (ρ RMS = 0.2-0.5 nm) (2,16). However, thicker (20-to 50-nm) single-layer films are significantly more porous and rougher (ρ RMS > 1 nm) (2,16), reminiscent of conventional thick sol-gel oxide films (17)(18)(19)(20)(21). In this work, atomic force microscopy and SEM images show that optimized single-layer SCS growth yields smooth thicker oxide films ( 5 at low operating voltages of 2 V owing to the enhanced capacitance of the gate dielectric ( Fig.…”
Section: Significancementioning
confidence: 99%
“…Recently, this laboratory reported a low-temperature solution method, spin-coating combustion synthesis (spin-CS), for fabricating MO TFTs (SI Appendix, Fig. S1) (2,16). By incorporating an oxidizer and a fuel in the precursor solution, localized, highly exothermic chemical transformations occur within the spin-coated films, effecting rapid condensation and M-O-M lattice formation at temperatures as low as 200-300°C, which was assessed by thermal and X-ray diffraction (XRD) analysis, and yielding high-performance TFTs.…”
mentioning
confidence: 99%
“…Zinc oxide (ZnO) is one of such semiconductor [2] and especially because of nontoxicity [3], reasonably good crystallinity [4], high electron mobility [5] and light weight [6], they are widely used for channel material in TFTs [7]. Recently several metals like In, Sn, Ga [8] have been successfully doped into pure ZnO and subsequently IZO [9] (In doped ZnO), ZTO (Sn doped ZnO) [7], IGZO (In,Ga doped ZnO) [10] have been employed as channel material in order to further improve device performance [9], [11], [12] , [13]. But most of those dopants are either expensive or need process conditions such as higher temperature (>300 °C ), high vacuum for thin film formation which do not allow them in low cost flexible electronic applications [14].…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16] In general, metal oxide semiconductors on SiO 2 gate insulators are annealed at 200-500 C to form a coherent interface between the semiconductor and the gate insulator.…”
Section: Introductionmentioning
confidence: 99%
“…We chose a recently reported simple method for the amorphous IZO deposition in which the precursor solution is composed of zinc nitrate, indium acetylacetonate and 2-methoxyethanol. 16 Cho et al reported that 350 C-annealed IZO TFTs with SiO 2 gate insulators exhibited mobilities up to 13.8 cm 2 V À1 s À1 . 16 Although amorphous IZO channel layers with a smooth surface were well-formed on SiO 2 gate insulators, the formation on K-PIB gate insulators should be conrmed for the TFT application.…”
mentioning
confidence: 99%